Estudo de adsorção gás-sólido de hidrocarbonetos policíclicos aromáticos em diferentes adsorventes - Brudi, Letícia Callegaro (2020)
The extraction and the gas-solid adsorption behavior of different polycyclic aromatic hydrocarbons (PAHs) were studied in aqueous solution and in four different asphalt petroleum cement (APC) samples, using high-performance liquid chromatography as methodology analysis. Through extraction tests in aqueous solution at 50 ºC, 100% acenaphthene, 87,30% anthracene and 86,23% fluoranthene were emitted. Regarding the emissions of APC samples at 130 ºC, a total of 32,94 mg Kg-1 of total PAHs from the REGAP sample was obtained, which was selected as a representative sample for adsorption studies; 3,37, 3,64 and 1,46 mg Kg-1 of total PAHs of the AMP, REFAP and LUBNOR samples, respectively. Through tests of the evaluation of the retention capacity using three different masses, it was observed in aqueous solution that the, PUF (adsorption yields of 100%) and XAD-2 (adsorption yields>90%) showed the greater retention capacity for PAHs, followed by HDPE (adsorption yields 75-90%). For Si, EVA and GAC, the adsorption yields depended strongly on the PAHs. Alternatively, for the asphalts samples, the adsorption yields decreased for all the evaluated PAHs, showing that the asphalt matrix had the strong influence on the adsorption process, with the total PAHs being 47,20% for PUF, 46,80% for XAD-2, 29,90% for GAC, 27,30% for Si and 19,80% for HDPE. The retention and elution processes on the adsorbent surfaces were also evaluated by atomic force microscopy (AFM).